Educational System Innovation Through Collaboration Between Universities And Industry; (Case Study Program At Vocational University Of Brawijaya) - San Rudiyanto; Amelia Ika Pratiwi; Vinna Sukmawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2020)
The purpose of this study was to determine the concept of an Industrial collaboration system (collaborative system) in the Vocational Education Program of Universitas Brawijaya. This study uses a descriptive exploratory method in order to obtain comprehensive knowledge digging. especially related to the collaborative system implemented.